Regulatory Amendments of The Strategic Policy for The Job Creation in Indonesia: Research and Innovation Aspect - Prakoso Bhairawa Putera; Ida Widianingsih; Sinta Ningrum; Suryanto; Yan Rianto (ASEAN Journal on Science and Technology for Development, 2022)
The Job Creation Law, enacted in Indonesia in November 2020, has provided a new understanding of the sectors, such as investment and business activities, employment, and ease of conducting business, that are directly related to various aspects of regulatory adjustment. Research and innovation related to regulatory adjustments have received growing attention in recent years. This article thus attempts to reveal regulatory amendments from the strategic policy of job creation, particularly in terms of research and innovation, grouped into four topics: 1) conducting research and innovation activities; 2) supporting human resources and expertise; 3) stipulating policy support for facilitation, licensing, and taxation; and 4) endorsing the institutional implications of research and innovation in the regions.